2014
DOI: 10.1175/mwr-d-13-00200.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonglobal Parameter Estimation Using Local Ensemble Kalman Filtering

Abstract: Abstract. We study parameter estimation for non-global parameters in a low-dimensional chaotic model using the local ensemble transform Kalman filter (LETKF). By modifying existing techniques for using observational data to estimate global parameters, we present a methodology whereby spatially-varying parameters can be estimated using observations only within a localized region of space. Taking a low-dimensional nonlinear chaotic conceptual model for atmospheric dynamics as our numerical testbed, we show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…Bellsky et al () estimated non‐global parameters in the Lorenz '96 system, and found an important impact of the localization on the analysis quality, in particular some values of the localization radius, produce a significant improvement in the experiments they conducted, compared to the filter without localization. We did some preliminary experiments with our settings and we did not find a significant sensitivity to the localization radius so that we present results only without localization.…”
Section: Methodsmentioning
confidence: 99%
“…Bellsky et al () estimated non‐global parameters in the Lorenz '96 system, and found an important impact of the localization on the analysis quality, in particular some values of the localization radius, produce a significant improvement in the experiments they conducted, compared to the filter without localization. We did some preliminary experiments with our settings and we did not find a significant sensitivity to the localization radius so that we present results only without localization.…”
Section: Methodsmentioning
confidence: 99%
“…The problem of joint state-parameter estimation has been investigated in many previous studies. To deal with the uncertainty of model parameter in the context of DA, a commonly used DA approach such as an ensemble Kalman filter (EnKF; Evensen 1994;Houtekamer and Mitchell 1998) or local ensemble transform Kalman filter (LETKF) in Ott et al (2004) has been adapted by augmenting the state vector with the uncertain parameters; hence, the augmented method (Aksoy et al 2006;Annan et al 2005;Baek et al 2006;Bellsky et al 2014;Carrassi and Vannitsem 2011;Gillijns and De Moor 2007;Koyama and Watanabe 2010). The standard Kalman update equations are then applied to estimate the combined state-parameter vector.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to avoid this difficulty is the interacting Kalman filter whereby two Kalman filters are designed to estimate states and parameter separately and the two filters interact (Friedland 1969;Koyama and Watanabe 2010;Moradkhani et al 2005). A more recent approach to this problem also successfully deals with the local variability of parameters by using the augmented LETKF (Baek et al 2006;Bellsky et al 2014;Kang et al 2011). This approach computes the Kalman update equations for the subdivided local regions in parallel with a dimensionally reduced state vector.…”
Section: Introductionmentioning
confidence: 99%
“…strategically targeting observations to reduce state estimation and forecast error; 3-16 2. estimating model parameters [17][18][19][20][21][22] within the targeting observation context to further reduce estimation error.…”
Section: Introductionmentioning
confidence: 99%
“…The main part of our numerical results investigates estimating parameters for the chaotic Lorenz-96 model, where we expand on previous literature by applying recently developed parameter estimation techniques [18][19][20] within the novel context of targeted observations. Model parameters are typically fixed quantities that encode physical information about a dynamical system which are often estimated within large weather and climate models.…”
Section: Introductionmentioning
confidence: 99%